Trial cultivation of two strains Spirulina platensis CNT and Spirulina platensis C1 in medium with different mineral water resources such as Thach Thanh - Thanh Hoa, Thanh Tan - Thua Thien - Hue and Thanh Liem - Ha Nam province - Nam, Hoang Sy; Hong, Dang Diem (Academia Journal of Biology, 2014)
Trial cultivation of two strains Spirulina platensis CNT and Spirulina platensis C1 in medium with different mineral water resources such as Thach Thanh - Thanh Hoa, Thanh Tan - Thua Thien - Hue and Thanh Liem - Ha Nam province